CAPITOSAURID AMPHIBIANS FROM THE UPPER LUANGWA VALLEY, ZAMBIA - Chernin, Sharon (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1974)
The purpose of this paper is to describe two capitosaur skulls from the Luangwa valley, Zambia. A tentative decision is made assigning the material to Parotosaurus pronus (Howie, 1969). The stratigraphy of the locality in which the material was found and that of the type species is discussed. A possible mechanism for opening the mouth of capitosaurs is put forward, with the qualification of its success depending on the animals being neutrally buoyant.